2023
DOI: 10.1029/2023ja031541
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the Harmonic Frequency Separation of Ionospheric Alfvén Resonances at Eskdalemuir Observatory, UK

Abstract: We extracted the harmonic frequency separation (Δf) of Ionospheric Alfvén Resonances (IAR) observed in the Eskdalemuir induction coil magnetometer data for the 9 year data set of 2013–2021. To obtain Δf values, we used a machine learning technique that identifies the harmonics and from this we calculated the average separation. To investigate the climatology of the IAR, we have modeled the Δf of the IAR for the data set using a time of flight calculation with model Alfvén velocity profiles. When analyzing Δf f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…This demonstrates that the time-of-flight calculation of Δf accurately describes the separation of higher harmonics, but not the frequency of the fundamental, resulting in an offset of the harmonics and Δf, which was noted by Hodnett et al (2023). This offset is not constant, which is a result of the non-uniformity of the ionosphere, which we next analyze.…”
Section: Comparing Modeled and Observed Frequenciesmentioning
confidence: 82%
See 4 more Smart Citations
“…This demonstrates that the time-of-flight calculation of Δf accurately describes the separation of higher harmonics, but not the frequency of the fundamental, resulting in an offset of the harmonics and Δf, which was noted by Hodnett et al (2023). This offset is not constant, which is a result of the non-uniformity of the ionosphere, which we next analyze.…”
Section: Comparing Modeled and Observed Frequenciesmentioning
confidence: 82%
“…Overall, we find 12,488 time bins in the data where five harmonics have been identified by the U-net, across the 9-year data set. This is fewer than the number of points used in the study from Hodnett et al (2023), as previously we used a less constrained approach and found times where at least four harmonics were identified to obtain Δf, rather than five. These instances where at least five harmonics were identified occurred over 644 separate days.…”
Section: Extracting Iar Frequencies From Magnetic Field Measurementsmentioning
confidence: 92%
See 3 more Smart Citations